Men's help‐seeking in the first year after diagnosis of localised prostate cancer - Hyde, M.K. (Eur J Cancer Care (Engl), 2016)
This study describes sources of support utilised by men with localised prostate cancer in the first year after diagnosis and examines characteristics associated with help‐seeking for men with unmet needs. A cross‐sectional survey of 331 patients from a population‐based sample who were in the first year after diagnosis (M = 9.6, SD = 1.9) was conducted to assess sources of support, unmet supportive care needs, domain‐specific quality of life and psychological distress. Overall, 82% of men reported unmet supportive care needs. The top five needs were sexuality (58%); prostate cancer‐specific (57%); psychological (47%); physical and daily living (41%); and health system and information (31%). Professional support was most often sought from doctors (51%). Across most domains, men who were older (Ps ≤ 0.03), less well educated (Ps ≤ 0.04) and more depressed (Ps ≤ 0.05) were less likely to seek help for unmet needs. Greater sexual help‐seeking was related to better sexual function (P = 0.03), higher education (P ≤ 0.03) and less depression (P = 0.05). Unmet supportive care needs are highly prevalent after localised prostate cancer diagnosis with older age, lower education and higher depression apparent barriers to help‐seeking. Interventions that link across medicine, nursing and community based peer support may be an accessible approach to meeting these needs. Clinical Trial Registry: Trial Registration: ACTRN12611000392965.